Tingkat Kecemasan Guru Taman Kanak-Kanak Dalam Pembelajaran Jarak Jauh Di Kota Tasikmalaya - Zulfa Azkiya; Elfan Fanhas Fatwa Khomaeny; Fajar Nugraha (UIN Sultan Maulana Hasanuddin Banten, 2022)
Learning during the COVID-19 pandemic was turned into distance learning. In this COVID-19 pandemic situation, the learning process does not run as usual, with this situation causing anxiety for teachers in general. This study aims to determine the level of anxiety of Kindergarten teachers in Distance Learning in Tasikmalaya City. Therefore, to determine the level of teacher anxiety, a research was conducted using descriptive quantitative research methods through distributing questionnaires based on the anxiety theory of Robert L Spitzer which consisted of 7 instruments (GAD-7). The population in this study amounted to 407 teachers, and the number of samples in this study amounted to 202 teachers. This research uses google form. The results of the study of 218 people showed that the level of anxiety of kindergarten teachers in PJJ in Tasikmalaya City was in the category of moderate anxiety with a percentage value of 47.2%, with the difference in anxiety levels in the category of not having anxiety was 3.2%, while the difference in anxiety levels in the category of not having anxiety was 3.2%. the low category is 11.9% and the difference in the high level of anxiety category is 37.6%. Keywords: Anxiety, Kindergarten, Distance Learning References Afiani Rara. (2020).“Inovasi Teknologi Dalam Pembelajaran Pada Masa Pandemic Covid-19 Di MI Nurul Yaqin, Al Amin, M. N. K. (2020). Menakar Nilai Kemanfaatan dari Penangguhan Walimat Al- ‘Ursy Di Masa Darurat COVID-19 Melalui Sadd Adz-Dzari’ah. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 10(1), 27–38. Allen, Jennifer L., and Rebecca Lerman. (2018).